PELAKSANAAN DEPONERING DALAM PERSPEKTIF ASAS EQUALITY BEFORE THE LAW - Kurnianto, Diska; Susila, Agna; Kurniaty, Yulia (Fakultas Hukum Universitas Muhammadiyah Magelang, 2017)
This study examines and analyzes related criminal cases abuse in the criminal justice system in Indonesia under Law No. 16 of 2004 on the Prosecutor of the Republic Indonesia by closing a criminal case under the Code of Criminal Procedure (Criminal Procedure Code). This research method using a normative juridical approach to law (Statute Approach). Primary legal materials, secondary, and tertiary obtained by the author will be analyzed using analytical techniques interpretation of the law, namely: Content Analysis, which is used as a reference in resolving legal issues that become the object of study.        From the research results to the above method, the authors obtain answers to existing problems that the implementation case abuse accordance with the principles of opportunity in Article 35 letter c of Law Number 16 of 2004 on the Prosecutor of the Republic of Indonesia is still relatively small only be carried out by the Attorney General as the head chief prosecutor Court of the Republic of Indonesia in excluding criminal cases, and the closure of the case can be implemented by all prosecutors as the public prosecutor (prosecutor) without a process of public interest but can only be enforced closure of the case in the interest of law-related problems that menyangkat communities concerned in criminal cases.